Validation of High Aims 65 Score in Patients with Variceal Bleed - Saeed, Aafia; Haq, Muhammad Mansoor ul; Rahat, Adeel (Pakistan Armed Forces Medical Journal, 2025)
Objective: To validate high AIMS 65 score for predicting 30-day mortality in patients with variceal bleed presenting to a tertiary care hospital.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Gastroenterology, Liaquat National Hospital Karachi, Pakistan from Aug 2021 to Apr 2022.Methodology: Cirrhotic patients having variceal bleeding requiring hospital admission, aged 18-60 years of either gender, with history of hematemesis and/or melena were assessed clinically and enrolled into the study after taking consent. All the patients underwent esophagogastroduodenoscopy at the endoscopy suite. Laboratory investigations were done upon their hospital admission to figure out the AIMS 65 score. Patients’ demographic and clinical details were documented in a pre-designed proforma by the assigned data collectors.Results: 267 patients were enrolled with median age of 57(interquartile range=50-63) Median CLD duration of 48 months (IQR=36-60). There was a predominance of male patients (67.4%). Majority of the patients had AIMS score of 2(56.2%) whereas 43.8% had score of 3.30 days whereas mortality was observed in 19.1% of the cases. The frequency of mortality was significantly higher in patients having AIMS score of 3 as compared to AIMS score of 2 (70.1% versus 29.9%, p